2016
DOI: 10.1177/2048872616683635
|View full text |Cite
|
Sign up to set email alerts
|

Early increase in serum fatty acid binding protein 4 levels in patients with acute myocardial infarction

Abstract: FABP4 levels were significantly elevated during the early hours after the onset of AMI and were robustly increased in OHCA survivors. Together with the finding that FABP4 is released from adipocytes via β3-AR-mediated lipolysis, our data provide a novel hypothesis that serum FABP4 may represent the adrenergic overdrive that accompanies acute cardiovascular disease, including AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…The coronary veno-arterial difference in FABP4 levels in the aortic root and coronary sinus was shown to be an independent predictor of the severity of coronary stenosis after adjustment of conventional risk factors 35) . FABP4 levels are significantly elevated during the early hours after onset of acute myocardial infarction and are robustly increased in out-of-hospital cardiac arrest survivors, probably due to rapid lipolytic release of FABP4 from epicardial fat by adrenergic overdrive that accompanies acute cardiovascular disease 104) .…”
Section: Circulating Fabp4 Levelmentioning
confidence: 99%
“…The coronary veno-arterial difference in FABP4 levels in the aortic root and coronary sinus was shown to be an independent predictor of the severity of coronary stenosis after adjustment of conventional risk factors 35) . FABP4 levels are significantly elevated during the early hours after onset of acute myocardial infarction and are robustly increased in out-of-hospital cardiac arrest survivors, probably due to rapid lipolytic release of FABP4 from epicardial fat by adrenergic overdrive that accompanies acute cardiovascular disease 104) .…”
Section: Circulating Fabp4 Levelmentioning
confidence: 99%
“…Without serial testing of FABP4 levels, we yielded no data regarding the change of FABP4 levels in those nondiabetic stroke patients. Interestingly, one study reported significantly elevated FABP4 levels during the early hours after the occurrence of acute myocardial infarction [51]. In addition, cerebrospinal fluid samples were not obtained.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, elevation of circulating FABP4 occurs when GFR is markedly reduced or abolished. Circulating FABP4 is negatively correlated with GFR and markedly increased up to 20-fold in patients undergoing maintenance hemodialysis 8 , 10 12 . We showed that BLN induced marked elevation of circulating FABP4.…”
Section: Discussionmentioning
confidence: 99%
“…FABP4 is secreted from adipocytes despite the lack of an N-terminal secretory signal sequence via ER-Golgi-independent pathways 5 7 . Secretion of FABP4 is enhanced by lipolysis, which is accelerated during fasting and activation of sympathetic nervous system in a β-adrenergic receptors-dependent manner 5 , 6 , 8 , 9 . On the other hand, FABP4 is likely to be eliminated from the circulation mainly by renal clearance 10 12 .…”
Section: Introductionmentioning
confidence: 99%